2014
DOI: 10.2147/sccaa.s38006
|View full text |Cite
|
Sign up to set email alerts
|

Direct reprogramming of adult cells: avoiding the pluripotent state

Abstract: The procedure of using mature, fully differentiated cells and inducing them toward other cell types while bypassing an intermediate pluripotent state is termed direct reprogramming. Avoiding the pluripotent stage during cellular conversions can be achieved either through ectopic expression of lineage-specific factors (transdifferentiation) or a direct reprogramming process that involves partial reprogramming toward the pluripotent stage. Latest advances in the field seek to alleviate concerns that include tera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 102 publications
(159 reference statements)
0
48
0
Order By: Relevance
“…Induced pluripotent stem (iPS) cells can now be derived from a wide range of somatic cells via the over-expression of a cocktail of TFs [6] or a combination of TF expression with chemical compounds [7, 8]. Moreover, somatic cells can now be directly reprogrammed into entirely different cell types [9] through the expression of lineage-specific sets of transcription factors. Yamanaka's seminal discovery has introduced the concept that the fate of adult somatic cells can be controlled through TF expression.…”
Section: Introductionmentioning
confidence: 99%
“…Induced pluripotent stem (iPS) cells can now be derived from a wide range of somatic cells via the over-expression of a cocktail of TFs [6] or a combination of TF expression with chemical compounds [7, 8]. Moreover, somatic cells can now be directly reprogrammed into entirely different cell types [9] through the expression of lineage-specific sets of transcription factors. Yamanaka's seminal discovery has introduced the concept that the fate of adult somatic cells can be controlled through TF expression.…”
Section: Introductionmentioning
confidence: 99%
“…10 Interest is now focused on converting cell fates without going through a pluripotent intermediate. 1113 Multiple studies have demonstrated our ability to directly convert fibroblasts to other cell types, such as functional/spinal motor neurons, myelinogenic oligodendrocyte progenitor cells, neural stem cells, cardiomyocytes, striated mononucleated myoblasts, multinucleated myotubes, Sertoli cells, macrophages, and hepatocyte-like cells 1424 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The transdifferentiation process takes shorter time compared to iPSC generation 23 . Direct reprogramming is, therefore, a viable option for cell derivation in regenerative and personalized medicine application.…”
Section: Discussionmentioning
confidence: 99%